SOCIAL SUPPORT FOR THE QUALITY OF LIFE POSTPARTUM MOTHERS IN SUKODONO SUBDISTRICT SRAGEN REGENCY - Faizah Betty Rahayuningsih; Endang Zulaicha S (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2014)
Introduction: Postpartum period is often considered as temporary or unimportant thing. Thus, the postpartum treatment becomes the ignored aspect from the women's health. The social support is important for mother's and child's prosperity. This research is aimed to examine the difference and the influence of social support score and the quality of life postpartum mothers by home visit 1, 2, and 3. Method: This research employs cross sectional design with longitudinal repeated measure design. The sample of this research was postpartum mothers that give birth in the village of Sukodono subdistrict area from 3 to 40 days. The sample is selected by purposive sampling. Results: There is no significant difference of mean between husband's, parents', parents-in-law's, and relative's support (p > 0.05). There is no significant difference between the quality of life postpartum mother (p > 0.05). The regression equality of social support to quality of life pospartum mother in K1, K2, and K3 were 0,157 + 0.702*husband's support, 0.099 + 0.370*husband's support – 0.674*relative's support, and 0,123+0,0674*husband's support-0,633*relative's support, respectively. Discussion. Husband's support increase quality of life pospartum mother. This is suggested to plan education in-service about the important of social support after giving birth for midwife or nurse that has role to service the mothers. Giving the education of postpartum preparation is not only for the mothers, but also for their husband. Keywords: relative's support, quality of life, postpartum